Monitoring of students body posture: a longitudinal study. - Nichele, Lidiane de Fátima Ilha; Turra, Patrícia; Badaró, Ana Fátima Viero (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Childhood and adolescence are important periods of growth in which the position is altered to support the new body proportions. Objective: To characterize the longitudinal profile of body posture in children and adolescents. Method: Body posture of children and adolescents of a Philanthropic Institution was assessed through an initial and one final evaluation after 24 months. The postural evaluation was performed by means of photogrammetry according to the Software Protocol (SAPo v 0.68). For analysis of the variables, the sample was divided into two groups with respect to age, where the first group (GI) was composed of 17 children aged 6 to 7 years and the second group (GII) by individuals from 8 to 10 years. Statistical analysis was performed with the Statistical Package for Social Sciences 15.0 software (SPSS). The significance determination criterion used was the level of 5%. Results: 34 students (19 girls and 15 boys) were evaluated. In relation to body posture, when the initial and final evaluation were compared, the variables Q right angle (p = 0.003) and horizontal alignment of the pelvis (p = 0.006) showed significantly difference to the GI. To GII the variables horizontal alignment of acromions (p = 0.016), right frontal lower limb angle (0,019) and left (p <0.001), Q right angle (p = 0.001) and left (p <0.001), alignment horizontal pelvis (p = 0.009), ankle angle (p = 0.002) and left-leg/hindfoot angle (p = 0.017) showed greater changes in angular medians. Conclusion: Children of GI presented more homogeneous values after the established range, keeping an angular stability for most of the observed postural variables. However, GII presented more significant decreases in asymmetries and body misalignments.